Thermal stress analysis of different full and ventilated disc brakes (Fracture and Structural Integrity, 2015)
During the braking phase, the heat produced by friction between pads and disc cannot be entirely dissipated. Consequently, the brake disc, especially if very hard braking occur, can accumulate large amounts of heat in a short time so producing high gradients of temperature on it. Under these conditions, functionality and safety of the brake system can be compromised. The object of this study is to investigate, under extreme working conditions, the thermomechanical behaviour of different brake rotors in order to evaluate their efficiency and stability and to identify any compromising weakness on them. In particular, by means of FEM thermo-mechanical coupled analyses, one full disc and three ventilated rotors with different shapes have been studied. A very hard (fading) test has been used to evaluate the performances of the discs in terms of temperature distribution, stresses and strains. Obtained results demonstrate that the analysed ventilated discs, unlike the full rotor, can be effectively used in very hard working conditions, always ensuring high safety levels. Among the studied rotors, the curved-vanes disc was found to be the best solution.
Keywords: Ventilated disc